Perlindungan Hukum Nasabah Terhadap Risiko Perjanjian Kredit yang Mengutamakan Profitabilitas Bank dalam Perspektif Hukum Positif - Dirantha; Kalianda, Karlie Hanafi; Ayu , Riana Kesuma (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
Provision regarding credit agreement risks that prioritize bank profitability in credit agreement relationships. Banks implement the principle of prudence when disbursing credit. This is done to maintain a healthy and prudent banking system and the ability to protect the funds entrusted to it. Providing credit aims to seek profits in the form of interest as remuneration, administration fees and provisions received by creditors from debtors. These are the risks borne by banks, one of which is credit risk. The risk borne by the customer is that they must agree to a standard credit agreement; Moreover, a standard credit agreement is more profitable for the bank, which can include clauses that benefit the bank, such as an exoneration clause which frees the bank as a creditor from its obligations. In efforts to protect customers, apart from implementing UUPK, especially Article 18, BI policies are also outlined in Pillar VI in the API which covers four aspects, namely customer complaint mechanisms, the establishment of independent mediation institutions, transparency of product information and customer education.